Caracterización de las disfunciones acomodativas en estudiantes de la carrera de Optometría de la Universidad Técnica de Babahoyo, noviembre 2023 – abril 2024. - Obando Jaén, Ángelo Alexander (2024)
Accommodation is the process by which the convergence and dioptric power of the eye increases or decreases in order to perceive a near path stimulus. The malfunction of the accommodative system generates the appearance of alterations such as insufficient accommodative, excessive accommodation, accommodative spasm, accommodative inflexibility and accommodative paralysis. Objective: To characterize the accommodative dysfunctions in optometry students of the Babahoyo Technical University, period November 2023 – April 2024. Methodology: A cross-sectional, descriptive, quantitative and prospective approach was used, clinical histories served as the main fundamental basis for collecting background data, transcription of visual status and characterization of the various tests. Results: Tests such as monocular and binocular AA, FAM and FAB, ARN and ARP measurement, RA measurement and AC/A ratio were performed, where it was evidenced that accommodative inflexibility is the predominant alteration with 41.72% presenting variability in the visual system, followed by accommodative spam with 9.27%, excess accommodation 5.30% and with 3.31% accommodative insufficiency. Conclusions: The objective of characterizing the accommodative alterations was completed generating a report of the highest prevalence, demonstrating that the visual system in emmetropic and ametropic state, is apt to the appearance of accommodative problems.